Criatividade: caminho desenhante para altas habilidades/superdotação do adolescente em conflito com a lei - Peripolli, Arlei (2010)
The present scientific investigation had as basilar support, experiences that I had with adolescents in conflict with the law and the need for the investigative wanted promoted, so I proposed to research the topic of creativity, which becomes in this thesis. This was developed in line Research LP3 - Special Education in the area of high ability / giftedness. When confronted me with many questions that caused the issue, I was mobilized toward the search for clarifications, questioning the world around me and myself, with the goal of understanding what was unknown. Therefore, to help with the coping and listing some possible answers, it was delimitated as general aim to analyze descriptively the creativity in institutionalized adolescent as an indicator for high ability / giftedness and the understanding of it by teachers, evidencing them on pedagogical practicing. To help in this research, it was delimited by me some specific aims, such as: to describe some creative manifestation aspects in adolescents who are found in socio-educational standard, to check the understanding of teachers working at the Social Education Center - CASE - about creativity as an indication for high abilities giftedness; Identifying the developed teaching practices and investigate the dialogic relationship of theory and the practices of these teachers who assist this teenager. The individuals that cooperated were five State School Paulo Freire teachers, located within the CASE in Caxias do Sul - RS and two adolescents in conflict with the law and complying with social and educational standard in detention. The criteria used for choosing this target followed a few items of inclusion and exclusion. In regard to the teachers were considered those with longer effective exercise in teaching within CASE; who develop educational activities directly related to the teenager, working in Primary and Secondary education and the school management team. For adolescents, the priority was those within the age range of 12 to 18 years, with a longer detention staying and other recently picked up, one that was at the end of elementary school, another in high school and as a last option, both should be indicated by the searched teachers as being students with the highest creative ability compared to others. Thus, for answering to the aims and the study problematization, it was used on the descriptive research, with interpretation case study, given the heterogeneity and the search for consistency with the object in question. Descriptive because one of its purposes was to observe, retrieve, analyze, and to (co) relate the information that was obtained in interviews with the subjects investigated. For better interpretation of data, I used the qualitative analysis, because information confronted the reality that could not be quantified. To make the study of the evidence, we sought reasons in Narrative Analysis as the stories and the stories are commonplace in the daily life of the objects investigated. For collecting and recording of information were used as instruments: semi-structured notes in the logbook or field observations and recordings. Data analysis was carried out from these records and therefore allowed to produce inferences about the text, as all the interviews. Considering these statements and records of observations, I chose to do data analysis in the course of the chapters by juxtaposing the theoretical in evidence. The pedagogical practices which foster creativity have been implemented and are part of everyday life of this learning area. It was found that there is an explicit and constant concern in providing the development / expression of creativity through diagnosis, actions, resources, continuing education and participatory / collective management. The creativity study that I made resulted in defense of understanding as a faculty ontologically inherent to mankind, essential to its continued development process, although manifested uniquely, given the richness of existing diversity among humans and their relations to reality and, in the case of adolescents and the conflict with the law, is an indicative of high ability/giftedness.